ANALYSIS OF EXISTING METHODS AND APPROACHES TO THE ASSESSMENT OF RESIDUAL RESOURCES OF TRACTION ROLLING STOCK - Yusufov, Abdulaziz (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article presents an analysis of existing methods and approaches to assessing the residual life of elements of load-bearing structures of traction rolling stock. In this work, methods for assessing reliability indicators and reliability during the use of torsion action content are presented. The analysis of the characteristics characterizing the reliability of technical objects is presented. To confirm the validity of the forces acting on the motion, algebraic formulas are given.